Online scheduling protocol design for energy-efficient TWDM-OLT - Dutta, Sourav; Roy, Dibbendu; Bhar, Chayan; Das, Goutam (Journal of optical communications and networking, 2018)
The design of energy-efficient optical network units (ONUs) in passive optical networks (PONs) has been studied extensively in the literature. Time- and wavelength- division multiplexed PONs, a widely accepted future access technology, offer an additional opportunity to save energy at the OLT along with the existing energyefficient ONU design due to the idle periods (voids) created by scheduling. Existing proposals utilize few of the available wavelengths (active wavelengths) for scheduling, and energy efficiency is achieved by switching off the OLT receivers associated with the remaining wavelengths. In this paper we reason that, subject to a delay bound of the upstream data, the voids created due to scheduling in the active wavelengths remain unutilized and thus create ample opportunity for saving energy at the OLT. Further, we show that modifications of the conventional method provide a limited scope of utilizing these voids for energy efficiency. Thus, we deviate from the conventional methodology and propose a novel online scheduling protocol which aims at minimizing the number of voids in all wavelengths. Our results demonstrate a significant improvement in energy efficiency, as compared to existing proposals, without affecting the algorithmic complexity.